Hysteroscopic resection of type 3 fibroids could improve the pregnancy outcomes in infertile women: a case-control study - Ying Han; Ruqiang Yao; Yinfeng Zhang; Zexin Yang; Haining Luo; XinYan Wang; Aijun Du; Yunshan Zhang; Yingjun Zhu (BMC, 2022)
Abstract Background Type 3 fibroids are a special subtype of intramural fibroids that are likely to affect the pregnancy outcomes of assisted reproductive techniques. Hysteroscopic resection is a treatment for type 3 fibroids, but there has few study of its efficacy to date. In this study we evaluated the effect of hysteroscopic resection of type 3 fibroids on the pregnancy outcomes in infertile women. Methods This retrospective case-control study was conducted from January 1, 2014 to June 30, 2021. Patients who underwent IVF-ICSI in our unit were divided into a type 3 fibroid group and a hysteroscopic myomectomy group. The inclusion criteria for the type 3 fibroid group and the hysteroscopic myomectomy group were as follows: 1) age ≤ 40 years; 2) fibroid diameter or total fibroid diameter > 2.0 cm. The following exclusion criteria were used: 1) oocyte donor treatment cycles and 2) presence of chromosomal abnormalities; 3) history of other uterine surgery; 4) presence of intracavitary lesions, including submucosal fibroids; 5) single fibroid > 5.0 cm; 6) cervical fibroids; 7) unclear ultrasound description of fibroids; 8) preimplantation genetic testing was performed and 9) congenital or acquired uterine malformations. The control group in our study was selected from patients who were treated with IVF only because of fallopian tube factors. According to the age of the type 3 fibroid group and hysteroscopic myomectomy group, random sampling was carried out in the patients between 25 and 47 years of age to determine a control group. The outcomes measured included the average transfer times to live birth, cumulative clinical pregnancy rate, and cumulative live birth rate. Results A total of 302 cycles were enrolled in our study, including 125 cycles with type 3 fibroids, 122 cycles with hysteroscopic myomectomy, and 139 cycles of control patients. The average transfer times to live birth were significantly higher in the type 3 fibroid group than in the other two groups. The frequency of cumulative live births in the type 3 fibroid group was significantly lower than that in the control group. Compared with the control group, the hysteroscopic myomectomy patients had no statistically significant differences in the cumulative clinical pregnancy rate and cumulative live birth rate. Conclusions Type 3 fibroids significantly reduced the cumulative live birth rate of IVF patients. Ultrasound-guided hysteroscopic myomectomy can be used as a treatment for type 3 fibroids and could improve the pregnancy outcomes in infertile women.